Equivalence Strategy Used In Night At The Museum 2: Battle Of The Smithsonian Movie And Its Subtitle - Setianingsih, Diyah Hayu (2012)
This research studies the equivalence strategies in the Night at the museum 2: battle of the Smithsonian movie. The objectives of the study are to identify the types of equivalence subtitling strategy found in the movie and to describe the equivalency and the non-equivalency of the message found in Night at the museum 2: battle of the Smithsonian movie and its subtitle. The writer employs descriptive qualitative method. By this method, the writer uses the subtitling of Night at the museum 2: battle of the Smithsonian film as the data source, and the data are the written expressions containing equivalent strategy. The method of the data collection is documentation method.The collected data are analyzed by using Gottlieb's subtitling strategies theory. The method of analyzing the data is comparative method. The results of the research show that: first, the subtitling strategies used in the subtitle consisting of expansion, paraphrase, transfer, imitation, transcription, decimation, and condensation/deletion. From 321 data, the writer finds 328cases because 3 data contains more than one.There are 4. 6% or 15 cases belong to expansion, 4. 9% or 16 cases belong to paraphrase, 42% or 138 cases belong to transfer strategy, 10% or 34 cases belong to imitation, 1% or 3 cases belong to transcription, 5. 5% or 18 cases belong to decimation, and 32% or 104 cases belong to condensation/deletion strategy.The finding shows that the strategy on subtitling which is more commonly used in Night at the museum 2: battle of the Smithsonian movie is transfer strategy. Second, from 328 cases, there are 326 cases or 99% belong to equivalent and 2 cases or 1% belongs to non-equivalent.